The influence of training and motivation on teacher performance through competence as an intervening variable at the Islahul Ummah Foundation Probolinggo - Supristiwaningsih, Anita; Suswati, Endang; Nasir, Jamal Abdul (LP3M Universitas Islam Zainul Hasan Genggong, 2025)
Achievement of the vision, mission and goals of the organization will be achieved if its human resources show good performance. The purpose of this study is to (1) test and analyze the Effect of Training on Competence (2) test and analyze the Effect of Motivation on Competence (3) test and analyze the Effect of Training on Performance (4) testing and analyzing the Effect of Motivation on Performance (5) testing and analyzing the Effect of Competence on Performance (6) testing and analyzing the Effect of Training on Performance through Competence (7) testing and analyzing the Influence of Motivation on Performance through Competent Teachers in the Ishlahul Ummah Probolinggo Foundation. This research is a quantitative research. The data collection method used is a questionnaire. The sample used by the researchers was teachers at the Ishlahul Ummah Probolinggo Foundation totaling 66 people. In this study, the data were analyzed using path analysis or path analysis. The results showed that training (X1) had a significant influence on teacher competence (Z). Motivation (X2) has a significant effect on teacher competence (Z). Training (X1) has a significant effect on teacher performance (Y). Motivation (X2) has no significant effect on teacher performance (Y). Teacher Competence (Z) has a significant effect on teacher performance (Y). Indirectly Training (X1) through Competence (Z) has no significant effect on Performance (Y). Indirectly Motivation (X2) through Competence (Z) has a significant influence on Performance (Y).